Accounting transparency and the term structure of credit spreads - Yu, Fan (Journal of Financial Economics, 2005)
Theory predicts that the quality of a firm's information disclosure can affect the term structure of its corporate bond yield spreads. Using cross-sectional regression and Nelson-Siegel yield curve estimation, I find that firms with higher Association for Investment Management and Research disclosure rankings tend to have lower credit spreads. Moreover, this transparency spread is especially large among short-term bonds. These findings are consistent with the theory of discretionary disclosure as well as the incomplete accounting information model of Duffie and Lando (Econometrica 69 (2001) 633). The presence of a sizable short-term transparency spread can attenuate some of the empirical problems associated with structural credit risk models.